Evaluasi Surveillance Performa Waterflooding dengan Pendekatan Chan's Diagnostic Plot - Rahmadhini, Rahajeng; Suranto; Karina Larasati; Wicaksono, Dimas Suryo (Universitas Proklamasi 45, 2025)
Declining oil production as reservoir pressure decreases occurs because the reservoir's natural driving force is no longer able to force to the production well from porous permeable formation. The decline in oil production and reservoir pressure that occurs in the field over time necessitates the implementation of a second-stage oil recovery method (secondary recovery) that can replace the initial method (primary recovery). Secondary recovery method used in this study is water injection, or waterflooding. The objective of this research was to conduct a surveillance analysis of the waterflooding operation using the Chan's Diagnostic Plot approach to determine the connectivity between the wells involved in the operation. Water injection was implemented in oil reservoir in Field “RR” in 1995, and a second production peak was achieved in 1999 with an injection rate of 1,843 bwpd. water injection performance analysis in this study was carried out on the T-070T injection well against 2 production wells T-050 and T-111 using the Chan's Diagnostic approach to determine the connectivity between the waterflood impacted wells. Channeling was observed in that wells during waterflooding. This anaylsis indicates flow connectivity between the well T-070T and T-050/T-111